3D scanning and level of detail modelling for design and manufacturing - Fischer, A.; Park, S. (Hallwag Publishing Ltd, 1998)
3D scanning and modeling of manufacturing products play an important role in the rapid prototyping cycle. In order to achieve accurate reconstructed products, points are sampled at high density. However, for reconstruction, conventional methods usually reduce the data homogeneously without taking shape behavior, such as curvature and topology, into consideration. As a result, essential characteristic details may be lost. In this paper, an advanced method for reconstructing progressive models is proposed. Through this method, the reconstructed geometric model is represented by hierarchical levels of detail. The option to explicitly control the levels of detail is essential for design, modeling and analysis. The main advantage of the approach is that the sampled points are significantly reduced to several levels of abstraction, while at each level the geometric behavior is preserved. That is, even at lower resolution levels, critical details are preserved. Moreover, the method has been extended to progressive time and geometric models for simulation and is demonstrated by several examples.
Keywords: Computer aided design; Mathematical models; Rapid prototyping; Scanning; Progressive models; Reverse engineering; Computer aided manufacturing